The Vietnam:second higher education project = (The World Bank in Vietnam (WB), 2006)
The Second Higher Education Project (HEP2) aims to increase the quality of teaching and research in universities in ways that improve the employability of graduates and the relevance of research in Vietnam. The project will achieve its objective through: (i) developing policy and building capacity at the central government level in the areas of governance, financing and quality assurance; and (ii) building capacity, relevance and autonomy at the university level. HEP2 comprises of three components, with the first being capacity building for policy development. It aims to develop policy and build capacity in policy development in the key areas of: (a) the organization of the higher education system and its governance at central and higher level institutions (HEI) levels; (b) the public supply- and demand-side finding of higher education; and (c) quality of students at entry and quality of services provided by HEIs. The second component is the capacity building for the university teaching and research. This component is designed to strengthen teaching and research in selected universities, by: (i) building management capacity in universities; and (ii) financing teaching and research innovation grant (TRIG) sub-projects in two groups of selected universities. The third component is the project management, monitoring and evaluation. It aims to support and ensure a smooth and effective implementation of the project.